Fiqh Siyasah Review of River Transportation Services License in PERBUP No 4 of 2014 Regarding Sea and River Transport Business Licensing - Bella Novianti; Irwansyah Irwansyah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
River transportation, especially by using getek, is one of the solutions for overcoming distance and time in Indonesia. However, government regulations in river transportation services need to be seen from the point of view of fiqh siyasa. The purpose of writing this journal is to provide an overview of siyasah fiqh on river transportation service permits, especially getek, in government regulation Number 4 of 2014. The case study was conducted in Selayang Baru District, Langkat Regency, North Sumatra. The research method used is qualitative with data collection techniques through interviews and observations. The results of the study show that river transportation services using getek in Selayang Baru District, Langkat Regency have fulfilled the requirements in government regulation number 4 of 2014. However, there are several aspects that need to be considered from the point of view of fiqh siyasa, such as the safety and health of passengers, fair rates, and improving the quality of service. Therefore, a synergy is needed between government regulations and Sharia values ​​in regulating river transportation services, especially getek, in Indonesia.